Vertical and Horizontal Support Pressure Along The Kulekhani Iii Hep Tunnel Alignment, Nepal - Panthee, Suman (Journal of Institute of Science and Technology, 2016)
Support pressure obtained in tunnel is considered as stresses for applied support. Therefore, estimation of support pressure in tunnel is important task for tunnel support design. Several equations are proposed to estimate support pressures. In this study, Barton equation was used for estimation support pressures along the tunnel of Kulekhani III HEP. The calculated support pressures were highly dependent on Q value and joint characteristics. Vertical and horizontal support pressures in the Marble and Quartzite followed the pattern as followed by Q but for other rocks support pressures were not only dependent on Q but had high influence of the joint characteristics. Support pressures obtained from the equation can also be used to estimate support pressure to some extent but modification is necessary. The equations can be considered for obtaining maximum support pressures for support design. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, page: 112-118